Investigating the potential of lead‐free double perovskite Cs2AgBiBr6 material for solar cell applications: A theoretical study - Raj, Abhishek; Kumar, Manish; Kumar, Arvind; Laref, Amel; Anshul, Avneesh (International journal of energy research, 2022)
Summary Recently, Silver‐Bismuth based lead‐free double perovskite solar cells (PSCs) have established their significance as a possible substitute for lead‐based absorber in the PSCs due to its higher stability and nontoxic properties. In the present work, lead‐free double perovskite Cs2AgBiBr6 compound has been used as an absorber in the layered structure of PSC. This compound has been studied in details for its physical properties (electronic and optical) using the first principle calculation. Additionally, a lead‐free PSC is designed in SACPS‐1D simulation software with cell configuration of FTO/TiO2/Cs2AgBiBr6/Spiro‐OMeTAD/Au and studied for its various parameters useful for its applications in PSCs. Initially, the device is optimized under experimental counterpart to validate the simulation study and further various other material parameters such as band‐gap, defect density, thickness of absorber, series resistance and operating temperature are optimized to deliver improved performance. The final optimized lead‐free double PSCs exhibited power conversion efficiency (PCE) of 6.68%, open‐circuit voltage (VOC) of 0.90 V, current density (JSC) of 11.09 mA/cm2 and fill factor (FF) of 66.61%. Further, different ETLs such as TiO2, SnO2, ZnO, IGZO and PCBM are simulated with proposed device configuration and found TiO2 and SnO2 as suitable ETL candidate for Cs2AgBiBr6 based lead‐free PSCs. Lead‐free double perovskite Cs2AgBiBr6 material for solar cell applications.